Dynamic Response of Ultra Violet Absorbing in Dunaliella sp - Moh. Muhaemin (UNIVERSITAS SRIWIJAYA, 2011)
Micosporine-like Amino Acid (MAA) which can be found in fresh water and marine microalgae. its accumulation may have a role as a response to UV exposure. The accumulation of MAA was found in both artificial and solar UV radiation. No clear correlation between response of MAA to UV exposure. Simak Baca secara fonetik Keywords: MAA, UV, Dunaliella sp